INDIKASI ADVERSE SELECTION PADA PESERTA NON PBI MANDIRI JAMINAN KESEHATAN NASIONAL (JKN) DI RS RAJAWALI CITRA BANTUL YOGYAKARTA - Sri Sularsih Endartiwi (Universitas Aisyiyah Yogyakarta, 2015)
This study aims to identify adverse selection on independent participants non PBI of National Health Insurance (JKN) in RS Rajawali Citra Bantul, Yogyakarta. This research is quantitative descriptive with cross-sectional design.The results of the study show that in April 2014 the patients were hospitalized in the hospital Rajawali Citra has a of 100% month on the card printed with the date SEP BPJS is for 0-3 months. After BPJS applying for 7 days waiting period, it was found that in December 2014 to 9 peoples who have monthly difference of 0-3 months. In August 2015, after BPJS applying 14-days waiting period for patients who have a difference a month for 0-3 months between the date of the card printed with the date SEP BPJS it dropped to 3 people. This shows there is an indication of adverse selection on independent participants non PBI National Health Insurance (JKN) in RS Rajawali Citra Bantul. In addition, the application waiting period conducted by Health BPJS can suppress the occurrence of adverse selection on independent participants non PBI.Keywords: adverse selection, independent participants non PBI